Fiscal Transparency and the Performance of Government Financial Assets - Seiferling, Mike.; Tareq, Shamsuddin (Washington, D.C. : International Monetary Fund, 2015)
Stock-flow adjustments are typically measured as the difference between changes in gross debt and deficits. These are interpreted as a proxy for unexplained fiscal discrepancies, and often associated with a lack of fiscal transparency. However, such measures fail to capture the role of financial assets and valuation changes and therefore do not correctly predict fiscal transparency. The purpose of this paper is to provide a more detailed exposition of stock-flow residuals and the relationship with fiscal transparency, highlighting government acquisition of equities and investment fund shares and their performance in secondary markets. The results suggest that the performance of government equity portfolios correlates with fiscal transparency to the extent that fully transparent governments are expected to generate between 6 and 8 percent higher returns on their equity portfolios than others. These findings suggest that the performance of government assets may be a promising area for future research of fiscal transparency and stock-flow residuals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet